The level of Islamic religiosity of the local community and corporate environmental responsibility disclosure: evidence from Iran - Khodakarami, Mehdi (Journal of business ethics, 2024)
The purpose of this paper is to examine the relationship between the Islamic religiosity of the local community and the level of corporate environmental responsibility disclosure (CERD) in Iran, an example of an Islamic country. This paper also examines the moderating role of firm size, family ownership, and state ownership. This study is conducted using a sample of 952 observations across firms listed on the Tehran Stock Exchange. The results indicate that CERD increases with an increase in the level of Islamic religiosity of the province where the firm is located. In addition, findings reveal that firm size and family ownership strengthen the aforementioned relationship. However, we provide evidence suggesting that state ownership weakens the positive relationship between the Islamic religious atmosphere and CERD. The results of this research present a new insight suggesting that the Islamic values governing a local community can significantly affect executives' decisions regarding disclosures, particularly resulting in a decrease in executives’ selfishness and encouraging them to disclose more information about environmental responsibilities.